Clinical application value of metagenomic second-generation sequencing technology in hematologic diseases with and without transplantation - Zhang, Xia; Wang, Fang; Yu, Jifeng; Jiang, Zhongxing (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Hematological patients are at risk of infections. It is unknown whether the pathogenic microbial spectrum differs between HSCT and non-HSCT patients, and whether metagenomic next-generation sequencing (mNGS) of peripheral blood can be used as a substitute test specimen such as alveolar lavage. Methods A retrospective study was conducted to evaluate the clinical application value of mNGS in hematological patients with and without HSCT. Results Viruses were prevalent pathogens in both non-HSCT (44%) and HSCT (45%) patients, chiefly human cytomegalovirus and Epstein–Barr virus. In non-HSCT patients, Gram-negative bacilli accounted for 33% (predominantly Klebsiella pneumonia), and Gram-positive cocci accounted for 7% (predominantly Enterococcus faecium) of pathogens. However, in HSCT patients, Gram-negative bacilli accounted for 13% (predominantly Stenotrophomonas maltophilia), and Gram-positive cocci accounted for 24% (predominantly Streptococcus pneumonia) of pathogens. Mucor was the most common fungu s in two groups. The positive rate of pathogens by mNGS was 85.82%, higher than conventional detection (20.47%, P < 0.05). Mixed infection accounted for 67.00%, among which the mixed infection of bacteria and virus (25.99%) was the most common. 78 cases had pulmonary infection, the positive rate of traditional laboratory tests was 42.31% (33/78), and of mNGS in peripheral blood was 73.08% (57/78), showing a statistical difference (P = 0.000). The non-HSCT patients had a higher frequency of Klebsiella pneumonia (OR=0.777, 95% CI, 0.697-0.866, P = 0.01) and Torque teno virus (OR=0.883, 95% CI, 0.820-0.950, P = 0.031) infections than HSCT patients, while the rates of Streptococcus pneumonia (OR=12.828, 95% CI, 1.378-119.367, P = 0.016), Candida pseudosmooth (OR=1.100, 95% CI, 0.987-1.225, P = 0.016), human betaherpesvirus 6B (OR=6.345, 95% CI, 1.105-36.437, P = 0.039) and human polyomavirus 1 (OR=1.100, 95% CI, 0.987-1.225, P = 0.016) infections were lower. Leishmania could be detected by mNGS. Conclusion mNGS of peripheral blood can be used as a substitute test method for hematological patients with pulmonary infection, the detection rate of mixed infections by mNGS was high, and mNGS has high clinical recognition rate and sensitivity in pathogen detection, and provides a basis for guiding the anti-infective treatment in hematological diseases with symptoms such as fever.